Pendampingan Strategi Digital Marketing dan Pembayaran Online dalam Meningkatkan Produktivitas pada Penjualan Usaha Parfume Naza - Elsa Aprilia; Nanditha Sivanarianto; Pebri Badriyah; Pupung Purnamasari (Universitas Maritim AMNI Semarang, 2025)
In the midst of the increasingly rapid digital era, MSMEs in Indonesia, including the “Naza” perfume MSME in Cikarang, face challenges in increasing productivity and competitiveness. This community service activity aims to assist “Naza” perfume MSMEs in increasing productivity through assistance in implementing digital marketing strategies and online payments. By using qualitative methods which include observation, surveys and in-depth interviews as well as direct assistance. This service activity found that perfume MSMEs in Indonesia, including “Naza”, experience obstacles in utilizing the potential of digital marketing and online payments and it turns out that the implementation of digital marketing strategies through Instagram social media and online payments through QRIS and E-Wallet has succeeded in increasing product visibility, expanding market reach and increasing effective and efficient transactions. This service activity concluded that the importance of effective and efficient assistance for MSMEs in dealing with digital technology and competitiveness in the digitalization era to achieve sustainable growth.